Penerapan Balanced scorecard untuk meningkatkan kinerja Perbankan Syariah Sumatera Utara - Julian Helmi; Nazaruddin Nazaruddin; Harmein Nasution; Juliza Hidayati (Universitas Mercu Buana, 2021)
Islamic banking has enormous potential considering that Indonesia has the largest Muslim population in the world. The current performance measurement system for Islamic banks is still financial and non-financial, and there is an imbalance in the actual value of the company because it views financial and non-financial measurements as two important things that are not correlated. A comprehensive performance measurement system is urgently needed considering that Islamic banks must be able to follow market developments, such as the Balanced Scorecard. The aim of this research is to analyze the influence of the financial, customer, internal business, learning, and growth perspectives. Analyze which perspective is the most dominant in influencing the management performance of Islamic Banks. The results of the current research are Islamic banks in the growth stage towards the sustainability stage because they are supported by the application of goal-setting theory. Increasing employee performance satisfaction can be achieved by implementing an optimal system of leadership, motivation, and work spirit. This can be shown by the success of Islamic Banks in getting several awards from the business media.